Daily parenting of children with cerebral palsy: The role of daily child behavior, parents' daily psychological needs, and mindful parenting. (February 2021) - Dieleman, Lisa M.; Soenens, Bart; Prinzie, Peter; De Clercq, Lana; Ortibus, Els; De Pauw, Sarah S.W.
Abstract: The purpose of this study was to advance the current understanding of the daily dynamics that are involved in raising a child with Cerebral Palsy (CP). Specifically, we examined the role of mindful parenting and of day-to-day variation in parents' psychological needs and child behavior in explaining day-to-day variation in parents' autonomy-supportive, psychologically controlling, and responsive parenting behavior. Parents ( N = 58) of children with CP ( M age = 12.68 years) participated in a 7-day diary study. Multilevel analyses indicated that parents' autonomy-supportive, psychologically controlling, and responsive behaviors fluctuate considerably between days. Further, daily fluctuations in both child behavior and parents' own psychological needs were found to be associated with this daily variability in parenting. In addition, interindividual differences in mindful parenting were associated positively with parents' responsiveness and negatively with psychologically controlling parenting across the week. These findings point towards the changeability of parenting behavior among parents of a child with CP and suggest that interventions targeting parenting behavior in the context of CP will be most effective when taking into account both the parents' and the child's functioning.